Cambridge encyclopedia of Latin America and the Caribbean (Cambridge Univ. Press, 1992)
The book is structured in six parts: Physical Environment; Economy; Peoples; History; Politics and Society; and Culture. Designed in this way, the book is able to explore Latin America in all its diversity yet emphasise the regional and international trends of particular interest to non-spacialists. It examines urgent contemporary issues like economic and population growth, trade and international debt, tourism and the environment: the native flora and fauna, the emergence of early civilisations in Mexico and Peru, imperial domination over three centuries by Spain and Portugal, the struggle for independence in the nineteenth century, and the political turbulence of the twentieth. Coverage is provided also of music and literature, architecture, painting, and intellectual life, vividly reminding us that beyond today's headlines lies the culture of the tango and the samba, Borges and Neruda, García Márquez and Diego Rivera, Villa Lobos nad Bob Marley. Fifty-five maps, a glossary, more than 200 illustrations, and an index make the book a pleasure to use